2010
DOI: 10.1007/s00239-010-9426-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication and Divergence of Long Wavelength-Sensitive Opsin Genes in the Guppy, Poecilia reticulata

Abstract: Female preference for male orange coloration in the genus Poecilia suggests a role for duplicated long wavelength-sensitive (LWS) opsin genes in facilitating behaviors related to mate choice in these species. Previous work has shown that LWS gene duplication in this genus has resulted in expansion of long wavelength visual capacity as determined by microspectrophotometry (MSP). However, the relationship between LWS genomic repertoires and expression of LWS retinal cone classes within a given species is unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 62 publications
3
82
0
Order By: Relevance
“…The amino acid compositions of the spectrally effective sites, that is, 180, 197, 277, 285 and 308 of the four M/LWS-type opsin genes, were as follows: Ala, His, Tyr, Thr and Ala (designated Ala/His/Tyr/Thr/Ser), respectively, in LWS-1; Pro/His/Phe/Ala/Ser in LWS-2; and Ser/His/Tyr/ Thr/Ser in LWS-3 and LWS-4, as reported previously (Watson et al, 2011). The composition was invariant within and between populations except residue 180 of LWS-1 where an Ala/Ser polymorphism was found.…”
Section: Allelic Differentiation Of M/lws Opsins For Spectral Sensitisupporting
confidence: 76%
See 3 more Smart Citations
“…The amino acid compositions of the spectrally effective sites, that is, 180, 197, 277, 285 and 308 of the four M/LWS-type opsin genes, were as follows: Ala, His, Tyr, Thr and Ala (designated Ala/His/Tyr/Thr/Ser), respectively, in LWS-1; Pro/His/Phe/Ala/Ser in LWS-2; and Ser/His/Tyr/ Thr/Ser in LWS-3 and LWS-4, as reported previously (Watson et al, 2011). The composition was invariant within and between populations except residue 180 of LWS-1 where an Ala/Ser polymorphism was found.…”
Section: Allelic Differentiation Of M/lws Opsins For Spectral Sensitisupporting
confidence: 76%
“…We designed PCR primers (Supplementary Table S1) based on the untranslated regions of six opsin genes (SWS2-B, LWS-1, LWS-2, LWS-3, LWS-4 and SWS1), according to published sequences of Cumana guppy opsin genes (Watson et al, 2011) (GenBank accession numbers HM540108 and HM540107) and our unpublished data. The complete coding sequences of these opsin genes were amplified using these primers.…”
Section: Determination Of the Opsin Nucleotide Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Guppies have nine opsin types, named for the range of wavelengths detected: one short wave-sensitive-1 (SWS1: detecting ultraviolet), two short wave-sensitive-2 (SWS2: detecting blue/purple), two midwave-sensitive (RH2: detecting green), and four long wavesensitive (LWS: detecting red/orange) opsins (Hoffmann et al 2007;Ward et al 2008;Watson et al 2011). While all opsins are thought to play a role in color vision (Archer et al 1987;Archer and Lythgoe 1990;Watson et al 2011;Sandkam et al 2015), motion detection has been shown to rely most heavily on long-wavelength sensitivity, mediated by the L-class of cone cells, which contain LWS opsins (Anstis et al 1998;Schaerer and Neumeyer 1996;Krauss and Neumeyer 2003). Thus, a rebalancing of the trade-off between color vision (involving all opsins) and motion detection (involving primarily LWS opsins) can be measured by assessing differences in the proportion of opsins in the retina that are LWS opsins for fish reared in turbid water vs. clear water.…”
Section: Introductionmentioning
confidence: 99%